Strategy and Training - Korda, Philippe (Business Expert Press, 2012)
Ebook from IG Library ; This book explores corporate training in the context of deploying strategic initiatives within organisations. It goes beyond merely explaining strategy, to investigating how it relates to skills training, and how companies can leverage this to implement their initiatives. Drawing on real-life client examples and the inspirational stories of highly successful individuals, this book highlights approaches that have transformed organisations and re-invented training. It dispels myths that exist around traditional training paradigms and brings to light the effectiveness of new methods and approaches.